Implementasi Program Pemberdayaan Masyarakat Berbasis Ekonomi Kreatif Dalam Upaya Peningkatan Kesejahteraan dan Pencegahan Stunting di Desa Aek Najaji: Pengabdian - Ali Nurdin Siregar; Ahmad Nurul Fauzi; Febri Sri Rahayu Siregar; Naek Hot Martua Pane; Silvianna Sari Hutagalung (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
A Community Service Program (KKN) based on community empowerment through the creative economy was implemented in Aek Najaji Village, Padangsidimpuan, North Sumatra (October 2024-January 2025). This study analyzed the implementation and impact of the program on community welfare and stunting prevention using a participatory qualitative method involving 24 students and 614 community members. The program consisted of 18 activities in four areas (scientific, religious, arts-sports, thematic) with a total of 3,930 minutes of JKEM. The results showed significant improvements: participation in integrated health posts (Posyandu) increased by 30% (65% to 85%), household food diversity increased by 44% (3.2 to 4.6 food groups), the formation of 5 sustainable micro-enterprises with an average income increase of Rp 450,000/month, and 25 household gardens produced 15 kg of vegetables/month. The program successfully addressed the determinants of stunting through a holistic approach that integrates aspects of nutrition, environmental health, access to health services, and socio-economic empowerment. Despite facing infrastructure challenges and low youth participation (28%), the program achieved sustainability through the formation of eight community champions and an embedded system within the village structure.